Two new species of the mesopelagic isopod genus Syscenus Harger, 1880 (Crustacea: Isopoda: Aegidae) from the southwestern Pacific - Bruce, Niel L. (Zootaxa, 2005)
Syscenus moana sp. nov. and Syscenus karu sp. nov. are described. Syscenus moana, from off southern New Caledonia at depths of 1250–1410 m, differs from all species of Syscenus in having robust setae on the uropodal rami; S. karu, from off Vanuatu at depths of 450–480 m, is distinguished in particular from all but one species (S. peruanus Menzies & George, 1972) by the presence of eyes, and by stout pereopods.